Reductive Amination by Continuous-Flow Hydrogenation: Direct and Scalable Synthesis of a Benzylpiperazine - Liu, Jing; Fitzgerald, Anne E.; Mani, Neelakandha S. (Synthesis, 2012)
A benzylpiperazine was prepared directly from the corresponding benzaldehyde and piperazine on a continuous-flow hydrogenation apparatus. The synthesis was protecting group free, safe, and environmentally friendly. Large-scale synthesis under flow hydrogenation conditions was also demonstrated.
Keywords: amination; hydrogenation; green chemistry; benzylation; palladium